2017
DOI: 10.4103/jmp.jmp_105_16
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility study of a hybrid coplanar arc technique versus hybrid intensity-modulated radiotherapy in treatment of early-stage left-sided breast cancer with simultaneous-integrated boost

Abstract: This study demonstrated the feasibility and advantages of a hybrid, volumetric arc therapy technique that used two 90° coplanar arcs and two three-dimensional conformal tangential beams in the simultaneous-integrated boost radiotherapy of left-sided breast cancer after breast-conserving surgery. A total of nine patients with stage I, left-sided breast cancer who underwent breast-conserving surgery were selected for this retrospective study. For each patient, a hybrid arc plan was generated and then compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The researchers recommend H-VMAT for hypofractionated breast RT in DIBH due to reduced MU and treatment delivery time. Another study by Chen et al [27] consistently reported advantages of H-VMAT over H-IMRT with regard to dose conformity, heart dose, and delivery time. They compared H-VMAT with two different H-IMRT designs in the treatment of early-stage leftsided breast cancer.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The researchers recommend H-VMAT for hypofractionated breast RT in DIBH due to reduced MU and treatment delivery time. Another study by Chen et al [27] consistently reported advantages of H-VMAT over H-IMRT with regard to dose conformity, heart dose, and delivery time. They compared H-VMAT with two different H-IMRT designs in the treatment of early-stage leftsided breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“…The basis for proper dose application with H-VMAT to the patient is the existence of good reproducibility of the patient positioning. Dynamic techniques like H-VMAT may be prone to intra-and interfractional positioning uncertainties, which demand reproducibility of patient positioning both in treatment planning and execution [27,[29][30][31]. In order to minimize positioning uncertainties and deviations between planned and delivered dose distributions, CT acquisition and radiotherapy should be carried out in DIBH.…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques are not thoroughly implemented at each hospital, including the authors' institutions. In our manuscript,[ 1 ] we proposed hybrid plans (three-dimensional conformal radiotherapy [3DCRT] + intensity-modulated radiation therapy [IMRT] or 3DCRT + volumetric modulated arc therapy [VMAT]) solely for simultaneous integrated boost treatment delivery. As indicated in the manuscript, “The rationale of using two coplanar 90° arcs in the hybrid VMAT technology is as follows: (1) In the VMAT plan, two arcs are needed to optimize dose distribution when dealing with a complex target; (2) the target is an arc that was nearly 90° along the chest wall, and the 90° arc in tangential direction enters the target without irradiating much of the lung.” In the left breast irradiation, the target dose inhomogeneity and doses to the organs at risk (OAR), especially the heart, ipsilateral lung, and contralateral breast, are the major limitations of 3DCRT.…”
mentioning
confidence: 99%